Challenges and best practices of managing government projects and programs - Kwak, Young-Hoon; Liu, Min; Patanakul, Peerasit; Zwikael, Ofer (Project Management Institute, 2014)
Challenges and Best Practices of Managing Government Projects and Programs provides a crucial foundation for practitioners, researchers, policymakers, as well as constituents to realize the benefits governments can bring to their people.